SEM-PLS: ANALYSIS OF RELIGIOSITY AND THE COMPONENTS OF THE THEORY OF PLANNED BEHAVIOR ON HALAL TOURISM DECISIONS (International Journal of Cultural and Social Science, 2026)
This study aims to analyze consumer behavior toward halal tourism in West Sumatra using the Theory of Planned Behavior (TPB) framework extended by the construct of religiosity. The research is motivated by the need to understand how religious values are translated into halal tourism decisions that contribute to sustainable regional development. The study employs a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The variables examined include religiosity, attitude, subjective norm, perceived behavioral control, and halal tourism decision. The findings indicate that the extended TPB model explains 61% of the variance in halal tourism decisions, with attitude (? ? 0.453) and perceived behavioral control (? ? 0.398) emerging as the dominant factors. Religiosity does not have a direct effect but exerts a strong indirect influence through attitude (? 0.328) and perceived behavioral control (? 0.281). These results suggest that halal tourism behavior is primarily attitude-driven and control-driven, with religiosity serving as a psychological foundation that shapes positive attitudes and perceptions of ease in performing the behavior. The study concludes that religiosity plays a pivotal role in fostering sustainable and ethical tourism behavior among Muslim tourists. Practical recommendations include enhancing halal sustainability literacy, standardizing halal facilities, empowering community-based MSMEs and homestays, and strengthening evidence-based digital marketing and destination reputation management.